2016
DOI: 10.1111/1467-8454.12061
|View full text |Cite
|
Sign up to set email alerts
|

Does Ecological Footprint Impede Economic Growth? An Empirical Analysis Based on the Environmental Kuznets Curve Hypothesis

Abstract: This paper examines the relationship between income and environmental quality using environmental Kuznets curve (EKC) hypothesis. The hypothesised link is tested using time‐series analysis of 22 countries over the period 1961–2011. The degree of environmental impacts of economic activity is measured using ecological footprint (EF) per capita as explanatory variable, while real gross domestic product (GDP) per capita and its quadratic and cubic forms are used as predictor variables in these countries. First, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Though all the variables (except GFCF) show to be significant determinants of environmental degradation, energy use, per capita GDP, and financial development maintain their deteriorating impact across all model specifications. These outcomes are consistent with those of (Nathaniel 2020;Uddin et al, 2016;Nathaniel and Bekun, 2019;Omojolaibi and Nathaniel 2020;Ali et al, 2020;Sarkodie, 2018;Dogan et al, 2019;Meo et al, 2020;Nathaniel et al, 2020a,b,c,d).…”
Section: Static and Dynamic Analysis: Ecological Footprint Modelsupporting
confidence: 88%
“…Though all the variables (except GFCF) show to be significant determinants of environmental degradation, energy use, per capita GDP, and financial development maintain their deteriorating impact across all model specifications. These outcomes are consistent with those of (Nathaniel 2020;Uddin et al, 2016;Nathaniel and Bekun, 2019;Omojolaibi and Nathaniel 2020;Ali et al, 2020;Sarkodie, 2018;Dogan et al, 2019;Meo et al, 2020;Nathaniel et al, 2020a,b,c,d).…”
Section: Static and Dynamic Analysis: Ecological Footprint Modelsupporting
confidence: 88%
“…In (Kormishkina et al, 2019), based on analytical calculations, it is shown that an increase in real GDP accompanies the tightening of environmental policy in export-oriented countries. Uddin et al (2016) reached similar conclusions previously and examined the relationship between income and environmental (Beunen & Patterson, 2016;Collins et al, 2020) conclude that at the moment there is no effective compromise between the goals of environmental protection and the pursuit of economic benefits, which confirms the growth of the ecological footprint of humanity, creating an ecological debt to the planet. In 2020, the day when the world economy began to spend the planet's resources "on credit" came on August 22, and because of the coronavirus pandemic, it moved by almost a month.…”
Section: Problem Statementsupporting
confidence: 69%
“…In fact, several environmental performance indexes that capsulize various environmental indicators have been proposed. 71 The EF shows the human demand for natural resources, and it is one of the most comprehensive indicators of natural resource consumption currently available, 72 a comprehensive indicator of anthropogenic pressure on regenerative biological capacity, 73,74 and one of the most widely recognized measures of environmental sustainability. 75 The EF has been used by many EKC analysts as a dependent variable.…”
Section: Literature Reviewmentioning
confidence: 99%